Comparative Studies on the Distribution of some Useful Trees of Tropical Evergreen forests in the Western and the Eastern Parts of India - Rao, Rolla Seshagiri; Wadhwa, B. M.; Ansari, M. Y. (Indian Forester, 1961)
The present paper deals with the distribution of some useful timber species of Evergreen forests of both the Western and Eastern regions of India, together with their economic utility, and the need for introduction of such useful species from one region to another. An attempt has been made to include 84 species belonging to 33 genera which represent 16 families, some with their characteristic endemic features. A distribution table together with two maps indicating the occurrence of endemic species only in the evergreen forests of different states in Western and Eastern India and also two sets of photos each showing important species of respective evergreen forests have been added.